Emergent Bose liquid: A generic quantum state of matter alternative to Fermi liquid - Lang, Zi-Jian; Hegg, Anthony; Yildirim, Yucel; Jiang, Shengtao; Zou, Long; Yue, Xinlei; Ku, Wei (Elsevier, 2025)
With continuous success in understanding and predicting experimental results in various materials, Fermi liquid theory has undoubtedly been demonstrated to be the cornerstone of modern condensed matter physics. However, the applicability of this theory was challenged by the observation non-Fermi-liquid behaviors in strongly correlated materials. Here, we introduce a different quantum state of matter, namely an emergent Bose liquid formed from tightly bound pairs of neighboring fermions. Many features of this emergent Bose liquid, including transport properties, superconducting phase and critical points, Bose metal phase, non-Fermi-liquid scattering rate, pseudogap, and superconducting gap, all demonstrate qualitatively different behavior from Fermi liquid. Surprisingly, from room temperature down to the low-temperature limit and from the low-density to the high-density regime, we find good semi-quantitative agreement with (and simple explanations for) many observations without introducing free parameters beyond the initial tight-binding coefficients. Producing such a broad agreement with experiments from a single emergent Bose liquid model strongly supports this alternative quantum state of matter for understanding the physics of strongly correlated materials.
Keywords: Strongly Correlated Materials; Transport Properties; Superflow; Quasiparticle Properties